Strength of public preferences for endovascular or open aortic aneurysm repair. Issue 13 (20th November 2019) - Wickramasekera, N; Howard, A; Philips, P; Rooney, G; Hughes, J; Wilson, E; Aber, A; Michaels, J; Shackley, P
Abstract: Background: This study evaluated public preferences for the treatment processes for abdominal aortic aneurysm repair in order to allow them to be incorporated into a cost-effectiveness analysis. Methods: This was a telephone survey using a trade-off method in UK resident adults (aged at least 18 years) with no previous diagnosis of a vascular condition. Results: Some 167 of 209 participants (79·9 per cent) stated that they would prefer endovascular aneurysm repair (EVAR), 40 (19·1 per cent) preferred open surgery and two (1·0 per cent) stated no preference. Participants preferred EVAR because of the less invasive nature of the intervention and quicker recovery. Participants preferring open surgery cited reasons such as having a single follow-up appointment, and a procedure that felt more permanent. When participants were asked to make a sacrifice in order to have their preferred treatment, 122 (58·4 per cent) favoured EVAR, 18 (8·6 per cent) favoured open surgery and 69 (33·0 per cent) had no preference. Those preferring EVAR were willing to give up a mean of 0·135 expected quality-adjusted life-years (QALYs) to have EVAR, compared with a willingness to give up 0·033 expected QALYs among those preferring open repair. Conclusion: These results indicate a clear preference for EVAR over open surgery for aortic aneurysm. Graphical Abstract: There is a strong public preference for endovascular aneurysm repair (EVAR) because of quicker recovery times and less invasive attributes of EVAR. Public preferences for treatment process should be incorporated explicitly into the decision-making process. EVAR preferred